Translocation with targeted vaccination is the most effective strategy to protect an island endemic bird threatened by West Nile virus. Issue 9 (30th June 2020) - Bakker, Victoria J.; Sillett, T. Scott; Boyce, Walter M.; Doak, Daniel F.; Vickers, T. Winston; Reisen, William K.; Cohen, Brian S.; Hallworth, Michael T.; Morrison, Scott A.
Abstract: Aim: Invasive pathogens are a growing conservation challenge and often occur in tandem with rapid environmental transformation, such as climate change, drought and habitat loss. Climate change appears to have facilitated the spread of West Nile virus (WNV), a cause of widespread avian mortality. WNV is considered the primary threat to island scrub‐jays ( Aphelocoma insularis ), endemic to Santa Cruz Island, California. Two approaches have been proposed to safeguard island scrub‐jays: (a) vaccination and (b) conservation translocation to re‐establish a second population on neighbouring Santa Rosa Island, hypothesized to have a lower risk of WNV. These alternatives operate at regional scales but exemplify global concerns with strategic implications for conservation biogeography and climate adaptation. Location: California Channel Islands, USA. Methods: We compared the efficacy of vaccination and translocation strategies at minimizing 25‐year quasi‐extinction risk for island scrub‐jays using a stochastic population model. Results: Under current WNV‐free conditions, the predicted quasi‐extinction risk for island scrub‐jays was low (~0%) but increased to ≥22% with simulated WNV outbreaks. Vaccinating ≥60 individuals reduced risk to <5%, but risk doubled if population size declined and further increased with more frequent droughts. Translocation performed best if Santa Rosa Island had a large starting population size and habitat extent, and, more importantly, a low risk of WNV establishment; if Santa Rosa Island was inhospitable to WNV, quasi‐extinction risk dropped to near zero. Main conclusions: Translocation with targeted vaccination during high‐risk conditions was the most effective strategy to protect island scrub‐jays from West Nile virus. Although vaccination often outperformed translocation, only scenarios that included a Santa Rosa population and vaccinations achieved acceptably low species‐wide extinction risk across all potential future conditions. Our analysis informs strategies to improve the long‐term viability of the most range‐restricted bird species in the continental United States and provides a model for assessing conservation‐translocation proposals for other species and threats.